2008
DOI: 10.1121/1.2934488
|View full text |Cite
|
Sign up to set email alerts
|

Trim FEM simulation of a dash and floor insulator cut out modules with structureborne and airborne excitations

Abstract: During a vehicle development, measurements on cut out modules in large coupled reverberant rooms are often carried out in the middle and high frequency range in order to optimize the insulation performance of the trims (Transmission Loss). Using optimal controlled mounting conditions, we have been able to extend the frequency range to the low frequencies in order to validate trim FEM models of a dash and floor insulator modules with structureborne and airborne excitations. Both coupled response with movable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Finally, an example of an industrial application, courtesy of Faurecia (Duval et al 2008), is shown. The vibroacoustic response of a car floor module, excited by a shaker was measured at Faurecia labs.…”
Section: An Industrial Applicationmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, an example of an industrial application, courtesy of Faurecia (Duval et al 2008), is shown. The vibroacoustic response of a car floor module, excited by a shaker was measured at Faurecia labs.…”
Section: An Industrial Applicationmentioning
confidence: 99%
“…22 Example of the modelling of a fully trimmed car floor panel: (a) radiation problem, the floor panel is mechanically excited and radiates in a cavity; (b) transmission loss problem(Duval et al 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are many researches related to the dash panel, and they have reached many achievements. Duval [4] established the finite element model of the dash panel, computed transfer function and compared with experimental results. Results showed that they were consistent with each other.…”
Section: Introductionmentioning
confidence: 99%